2010
DOI: 10.1002/adfm.200901927
|View full text |Cite
|
Sign up to set email alerts
|

Compact and Light Supercapacitor Electrodes from a Surface‐Only Solid by Opened Carbon Nanotubes with 2 200 m2 g−1 Surface Area

Abstract: An approach is presented to make a “surface‐only solid” with a surface area of 2 240 m2 g−1 (1 310 m2 cm−3), corresponding to 85% of the atoms constituting a surface, by opening single‐walled carbon nanotube forests and solids via controlled oxidation. The controllability of the approach is demonstrated by tailoring the hole size to match the guest molecule, for example, nitrogen, fullerene, or solvated ions. These features make the surface‐only solid an ideal vessel for material and energy storage, as demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
103
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 153 publications
(107 citation statements)
references
References 38 publications
3
103
1
Order By: Relevance
“…This sample has a BET SSA of 2,285 m 2 g À 1 . The SSA of the graphene/CNT carpet hybrid material is comparable to the best reported values for open-ended CNTs (SSA 2,200 m 2 g À 1 ) 28 and graphene/graphene oxide (SSA 2,000B3000 m 2 g À 1 ) 29 11 , the new material is attractive, as it has an SSA close to the limits without sacrificing electrical properties.…”
Section: Resultssupporting
confidence: 50%
“…This sample has a BET SSA of 2,285 m 2 g À 1 . The SSA of the graphene/CNT carpet hybrid material is comparable to the best reported values for open-ended CNTs (SSA 2,200 m 2 g À 1 ) 28 and graphene/graphene oxide (SSA 2,000B3000 m 2 g À 1 ) 29 11 , the new material is attractive, as it has an SSA close to the limits without sacrificing electrical properties.…”
Section: Resultssupporting
confidence: 50%
“…Scanning electron microscopy (SEM) reveals the difference between the aligned well-defi ned structure of SWNT electrodes (Figure 1b ) and the random irregular structure of AC electrodes (Figure 1c ). In addition, the SWNT electrode is mesoporous, with a maximum pore size of 10 nm, [ 13 ] and has similar surface area to that of the forest (1250 m 2 g − 1 ). Infrared spectroscopy (Figure 1e ) and thermogravimetric analyses [ 15 ] (Figure 1f ) further confi rmed the presence of no chemicals other than carbon within the SWNT.…”
Section: Doi: 101002/adma200904349mentioning
confidence: 99%
“…In the infrared spectra, the peak after 0.3 e. V. is related to the S 11 transition associated with the bandgap energy of the semiconducting SWNTs present in the forest. [ 13 ] The SWNT electrodes fabricated have comparable density and thickness to conventional electrodes while preserving the intrinsic chemical purity and high surface area of the SWNT forest. While electrodes with lower densities and/or thinner thickness would inherently have higher power capability due to enhanced ion transport, such electrodes would be unable to meet the weight to have long lifetime as energy is stored physically.…”
Section: Doi: 101002/adma200904349mentioning
confidence: 99%
“…Therefore, there is a strong demand to develop new electrode materials to improve the energy density of EDLC. SWCNTs (Single-walled carbon nanotubes) have been expected as a good electrode material for EDLC because the theoretical specific surface area of SWCNTs is very large (2,630 m 2 /g) [1][2][3][4]. However, the reported EDLC capacitance values of SWCNTs are not so high compared to the values of the typical EDLC electrodes (e.g.…”
mentioning
confidence: 80%
“…In a previous study [7], the authors revealed that the cyclic voltammogram of SWCNT samples of high crystallinity and narrow diameter distribution had the shape of a dumbbell rather than either the typical rectangular shape obtained for other porous materials, or the butterfly shape previously reported for SWCNTs [3]. Fig.…”
Section: Resultsmentioning
confidence: 99%